Tata Sons Limited : 2010 - Dixit, Mukund R.; Bhowmick, Bhaskar (London : SAGE Publications Ltd, 2017)
This case provides an opportunity to develop criteria for the selection of a leader who would lead a well established conglomerate. It provides details about the initiatives of the predecessors, the changing environment of businesses, internal concerns and the challenges before the new leader. A list of the contenders for the top position in Tata Sons Ltd is given to facilitate evaluation. The participants are required to review the strategy and functioning of Tata Sons Ltd and develop their criteria for selection.
Originally published: Dixit, M., & Bhowmick, B. (2013). Tata Sons Limited: 2010. BP0356. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tata Sons Private Limited -- Case studies; Leadership -- India -- Case studies; Management -- India -- Case studies; Executive ability -- India -- Case studies